PENGARUH INTERNAL LOCUS OF CONTROL, NILAI-NILAI KERJA, TERHADAP KOMITMEN KARIR PADA TENAGA PENJUALAN DI INDUSTRI TELEKOMUNIKASI DI JAKARTA - Fadlillah, Alnisa Min (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
This research attempt investigated the impact of Locus of control, work values and on Career commitment with case study sales forces is in Telecommunication company (PT. Telkom Indonesia, Tbk, PT.Indosat Tbk, and PT. XL Axiata,Tbk ) located in Jakarta. 320 questionnaires were distributed, only 308 questionnaires were filled up by the respondents. Those data then were analyzed by using reability and validity test, correlation test and multiple regression analysis. The finding is supporting hypotheses from locus of control and work values which are submitted related with career commitment.